Potential of substitution of fertilizers by arboreal legume phytomass in coffee tree crop - de Oliveira, Heloísa Misae Tavares; Alvarenga, Maria Inês Nogueira; Melloni, Rogério; Cespedes, Juliana Garcia; da Cunha, Rodrigo Luz (Coffee Science - ISSN 1984-3909, 2015)
The use of arboreal legume phytomass in coffee cropping appears as an alternative way to improve the soil chemical properties and also to reduce production cost. The present paper aims to evaluate the effect of surface application of four arboreal legume phytomass (Cajanus cajan, Mimosa scabrella, Leucaena leucocephala and Acacia mangium) on soil chemical quality and verify the potential to substitute the use of chemical fertilizers (NPK) in coffee cropping under this management. This study was carried out at EPAMIG, in São Sebastião do Paraíso, MG, a Southern Brazilian experiment coffee cropping station. The phytomass of all legumes improved the soil chemical quality, especially Leucaena leucocephala, which also showed potential to reduce costs of NPK fertilizers on coffee cropping.